Significance of Water for Foundation of Dissipative Regulation of a Living Organism - Orzhelskyi , Igor; Kuznetsov , Andrey; Dijk , Elena Van (Advanced Research in Biological Science Vol. 9, 2024)
Water regulates homeostasis and supports metabolism by maintaining the balance of “bound-free” water phases. Dissipative processes of self-organization occur in both living and non-living matter. The same laws govern living and non-living matter, but the mechanism of their manifestation is different. The distinctive feature of living matter is “functional information,” which is an attribute characteristic only of living matter. The ideas of synergetics of self-organization are widespread in modern science. On their basis, the unity of living and non-living nature and the unity of micro- and macrocosms are established—the unity of the two opposites of chaos and order. Functional information is a purposeful indication of the change in the structural-functional state of the living matter. Feedback plays an essential role in self-organization and the dynamic balance of dissipative systems. Self-organization is based on positive feedback (PF). Dynamic equilibrium of the system is ensured by negative feedback (NF). There is a constant competitiveness between the two typ es of feedback - PF and NF. In biological systems, the balance of PF and NF is maintained based on auto-oscillatory homeostasis processes. In the hydration-dehydration processes of biopolymers, the dynamics of the ratio of bound to free water phases coincides with the regulating role of homeostasis. Water sustains the balance of the bound-free water phase ratio, which in turn maintains homeostasis.